Effect of dipole blockade on the laser excitation spectra of mesoscopic ensembles of cold Rydberg atoms. (June 2019) - Ryabtsev, I.I.; Beterov, I.I.; Tretyakov, D.B.; Yakshina, E.A.; Entin, V.M.
Abstract: The results of theoretical calculations of the multiatom laser excitation spectra of Rydberg atoms under conditions of a dipole blockade are presented, and the effect of the laser radiation line width and the interaction energy of Rydberg atoms on the dipole blockade completeness degree is discussed. It is shown that in order to increase the fidelity of performing quantum gates based on a dipole blockade, it is necessary to use resonance dipole − dipole interaction and exciting laser radiation with a line width smaller than 10 kHz.